Performance, Promotion, and the Peter Principle - Fairburn, J. A.; Malcomson, J. M. (Review of Economic Studies, 2001)
This paper considers why organizations use promotions, rather than just monetary bonuses, to motivate employees even though this may conflict with efficient assignment of employees to jobs. When performance is unverifiable, use of promotion reduces the incentive for managers to be affected by influence activities that would blunt the effectiveness of monetary bonuses. When employees are risk neutral, use of promotion for incentives need not distort assignments. When they are risk averse, it may—sufficient conditions for this are given. The distortion may be either to promote more employees than is efficient (the Peter Principle effect) or fewer. “Promotions serve two roles in an organization. First, they help assign people to the roles where they can best contribute to the organization's performance. Second, promotions serve as incentives and rewards.” (Milgrom and Roberts (1992, p. 364)) “Promotions are used as the primary incentive device in most organizations, including corporations, partnerships, and universities … This … is puzzling to us because promotion-based incentive schemes have many disadvantages and few advantages relative to bonus-based incentive schemes.” (Baker, Jensen and Murphy (1988, p. 600))